Functional MR cholangiography of the cystic duct and sphincter of Oddi using gadoxetate disodium: Is a 30‐minute delay long enough?. Issue 4 (21st September 2012) - Corwin, Michael T.; Lamba, Ramit; McGahan, John P.
Abstract Purpose: To determine if excreted contrast is consistently visualized in the gallbladder and duodenum after a 30‐minute delay using gadoxetate disodium‐enhanced MRI in patients without hepatobiliary disease. Materials and Methods: Twenty‐two patients without evidence of liver or biliary disease underwent gadoxetate disodium‐enhanced magnetic resonance imaging (MRI) from February 17, 2009 through October 3, 2011. The mean age was 45 years (range 25–72). T1‐weighted hepatobiliary phase images at 5, 10, 20, and 30 minutes after contrast injection were reviewed in consensus by two radiologists to determine the delay at which enhancement of the gallbladder and duodenum first occurred. Results: Thirteen of 22 (59.1%) patients demonstrated duodenal filling by 20 minutes and 16/22 (72.7%) filled by 30 minutes. The mean time to duodenal enhancement was 19.9 minutes (range 11.4–30.2 min). Seventeen of 22 (77.3%) patients demonstrated gallbladder filling by 20 minutes and 21/22 (95.5%) filled by 30 minutes. The mean time to gallbladder enhancement was 16.5 minutes (range 4.4–30.2 min). Conclusion: A significant number of normal patients do not show duodenal filling by 30 minutes, while the majority fill the gallbladder by 30 minutes using functional MR cholangiography (fMRC) with gadoxetate disodium. These findings will guide fMRC protocol design for patients with suspected acute cholecystitis and sphincter of Oddi dysfunction. J. Magn. Reson. Imaging 2013;37:993–998. © 2012 Wiley Periodicals, Inc.